Multimode interference devices and integration with electroabsorption modulators for photonic integrated circuits - Lee, Shuh Ying (2010)
The multi-mode interference (MMI) device is one of the Photonic Integrated Circuit (PIC) components. By manipulating the width and length of this device, light can be split either with different power ratio, different wavelength or different polarization, all of which have been investigated. MMI also functions as a 3dB splitter, very much like a directional coupler (DC). Discussion of their similarities and advantages has been included. By combining MMI devices to other devices, more functions can be integrated together. In this dissertation, the integration of MMI and electroabsorption modulators has been investigated. This integration involved the quantum well intermixing (QWI) process. By integrating modulators to a 1xN MMI, light from a single light source can be split into N paths, and these lights can be modulated separately.